Agricultura urbana: propuesta alternativa para la construcción del tejido social - Arévalo Martínez, Laura Vanessa; Cuesta Martínez, Yulixa Daniela; Sánchez Mesa, Yenifer Carolina (Corporación Universitaria Minuto de Dios, 2018)
This research is developed under theoretical references framed in the postulates of the paradigm of good living, the right to food, urban agriculture, food security, food sovereignty, social fabric, experience, social influence and motivations. Likewise, the research is based on the fundamentals of the interpretative approach, based on the paradigm of social constructionism and is carried out with a qualitative focus. This allowed the analysis of three experiences of urban agriculture at family, training and community level, in the locality of Engativa, in the neighborhoods, sector of Bachue II, Los Cerezos and Villa Cristina, in which, the strengthening of the social fabric through these processes is recognized, being developed from the different interests and motivations of the participants in these gardens.
La presente investigación se desarrolla bajo referentes teóricos enmarcados en los postulados del paradigma del buen vivir, el derecho a la alimentación, agricultura urbana, seguridad alimentaria, soberanía alimentaria, tejido social, experiencia, influencia social y motivaciones. Asimismo, la investigación se encuentra bajo los fundamentos del enfoque interpretativo, basada en el paradigma del construccionismo social y se realizó con una mirada cualitativa. Lo cual permitió el análisis de tres experiencias de agricultura urbana a nivel familiar, formativo y comunitario, en la Localidad de Engativá, en los barrios Bachue II sector, Los Cerezos y Villa Cristina, en las cuales se reconoció el fortalecimiento del tejido social por medio estos procesos, desarrollados a partir de los distintos intereses y motivaciones de los partícipes de estas huerta.
Keywords: Agricultura Urbana; Derecho a la Alimentación; Seguridad Alimentaria; Influencia Social; Trabajo Social; Calidad de Vida; Desarrollo Humano; Trabajo Social; Alimentos